VOLUNTEERING : EXPERIENCE OF SENIOR ADULTS - Gedvilienė, Genutė; Krunkaitytė, Marija; Trečiokienė, Edita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article deals with volunteering which in European Union is highlighted as one of the key possibilities for people to participate and include themselves into the international society life, solving various problems, such as poverty unemployment, public safety, organization of the meaningful leisure time. It analyzes communication and collaboration between international senior volunteers in two countries – Lithuania and Greece - sharing their experience in acquiring new abilities and skills, needed for knowledge-based society in the action based environment.